Integrasi VoiceThread dan TTSReader ke dalam Pembelajaran Bahasa Inggris Maritim untuk Meningkatkan Pengelolaan Kelautan dan Mendukung Kelestarian - Nyoman Ardiana Listriyawati; Dedy Kristiawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Akademi Maritim Nusantara Cilacap, 2025)
Artificial Intelligence plays a significant role in maritime studies. This research investigates how artificial intelligence (AI) can enhance English teaching in the marine studies sector, with a focus on marine management and environmental sustainability. Specifically, the research scope focuses on enhancing cadets’ vocabulary and comprehension related to sustainable ocean preservation, ensuring that learners not only acquire domain-specific terminology but also grasp the underlying concepts that promote ecological responsibility. Instructional tools based on artificial intelligence address the unique vocabulary and usage of maritime English, which pose particular challenges. These tools offer advantages such as personalised learning strategies, engaging simulations, and immediate feedback. Using a quantitative method with a pre-experimental design, this study examines the relationship between education, knowledge, and technological advancements in the education of cadets in maritime English. The research also addresses a gap in existing studies, which have primarily focused on vocabulary acquisition, by adding greater emphasis on enhancing comprehension of sustainable ocean preservation principles. The findings indicate that the VoiceThread and TTSReader significantly improve language skills and understanding of environmental conservation. It utilises both numerical data and qualitative feedback. Cadets demonstrated a twenty percent improvement in their language skills, a twenty percent rise in their average test scores, and a twenty- five percent improvement in their comprehension of sustainable ocean preservation approaches. Furthermore, the research emphasises the broader benefits of integrating artificial intelligence (AI) into maritime education, particularly in promoting a sustainable ethos in the naval sector. The supporting AI in education enhances language skills and fosters environmental consciousness in future maritime professionals, leading to improved marine management and enhanced ecosystem protection.